3D optical measurement and numerical simulation of the fracture behavior of Al6061 laser welded joints. (1st February 2019) - Tu, Haoyun; Schmauder, Siegfried; Li, Yan
Highlights: Strain fields on the surface of a transverse flat specimen are obtained with a DIC system (ARAMIS). Experimental strain fields obtained from ARAMIS are compared to the Rousselier simulation results. The Rousselier model is used to predict stress-strain curve and crack propagation of different specimens from welded joints. Abstract: In this paper, the fracture behavior of an aluminum laser welded butt joint was studied numerically and experimentally. With the assistance of a digital image correlation (DIC) system, the strain variation of the flat specimen under deformation is obtained. Void sheeting mechanism and shear bands are found on the surface of the specimen to precede rupture. Although initial pores are found in the fusion zone, good predictions are obtained with respect to stress-strain, F-COD as well as fracture resistance JR curves for flat and compact tension (C(T)) specimens, confirming the Rousselier model can predict the fracture behavior of aluminum laser welded joint well, with the Rousselier parameters calibrated from simulation of fracture behavior of notched round specimens.